Psychometric properties of the Chinese version of dermatology life quality index (DLQI) in 851 Chinese patients with psoriasis. (7th December 2011) - He, Z.; Lu, C.; Basra, M.K.A.; Ou, A.; Yan, Y.; Li, L.
Abstract Background The Dermatology Life Quality Index (DLQI) is one of the most frequently used scales to evaluate the impact of skin disease on patients' quality of life (QoL). There has not been psychometric evaluation of the Chinese version of DLQI in Chinese patients with psoriasis. Objective The objective of this study was to evaluate the psychometric properties of the Chinese version of DLQI. Methods Patients with psoriasis (≥18 years old) visiting nine hospitals in various regions of China were enrolled in the study. The DLQI, Psoriasis Disability Index (PDI) and Health Survey Short Form (SF‐36) were completed. Severity of psoriasis was assessed by the Psoriasis Area Severity Index (PASI). Reliability was estimated by internal consistency. Validity was assessed using known‐groups comparison, convergent validity and construct validity. Results In all, 851 patients were included in the study. The internal consistency reliability of the DLQI was high (Cronbach's alpha = 0.91). Known‐groups comparison showed that the DLQI discriminated well among patients who differed in age, geographical region, duration of psoriasis and the PASI score. Evidence of convergent validity of the DLQI was proved by high correlations with the PDI and four subscales of SF‐36 (role‐physical, bodily pain, social functioning and role‐emotional): r = 0.52–0.78. Construct validity was proved by the presence of one‐factor structure that accounted for 55.9% of the variance and fitted well into the unidimensional model. Conclusion The Chinese version of DLQI is a reliable and valid measure to assess patient‐reported impact of skin disease and could be used in QoL and health outcome studies on Chinese psoriasis patients.